Exploring the mode of action of inhibitors targeting the PhoP response regulator of Salmonella enterica through comprehensive pharmacophore approaches. Issue 16 (21st March 2019) - Tsai, Keng-Chang; Hung, Po-Pin; Cheng, Ching-Feng; Chen, Chinpan; Tseng, Tien-Sheng
Abstract : Comprehensive pharmacophore approaches explore the mode of action of inhibitors targeting PhoP response regulator of Salmonella enterica . Abstract : The PhoQ/PhoP two-component system regulates the physiological and virulence functions of Salmonella enterica . However, the mode of action of known PhoP inhibitors is unclear. We systematically constructed a pharmacophore model of inhibitors to probe the interface pharmacophore model of the PhoP dimer, coupling it with Ligplot analysis. We found that these inhibitors bind on the α5-helix, altering the conformation and interfering with PhoP binding on DNA.